Betulinic acid inhibits growth of hepatoma cells through activating the NCOA4-mediated ferritinophagy pathway. (March 2023) - Xiu, Zhiru; Zhu, Yilong; Li, Shanzhi; Li, Yaru; Yang, Xia; Li, Yue; Song, Gaojie; Jin, Ningyi; Fang, Jinbo; Han, Jicheng; Li, Yiquan; Li, Xiao
Graphical abstract: Abstract: Betulinic acid is found in the several foods and plants, such as sour jujube fruits, papaya, persimmon, betulinic acid exhibits low toxicity and a wide range of anticancer activities. Ferritinophagy and ferroptosis are related to tumor formation and therapeutic effects, both of which are controlled by iron metabolism and inextricably linked. In this study, we discovered that betulinic acid could suppress proliferation and migration of hepatoma cells, raised ROS level and inhibited antioxidation level in cells. Ferrostatin-1 was used to determine the death way of hepatoma cells induced by betulinic acid. Betulinic acid could cause ferritinophagy-related phenomenon in vivo and in vitro, promote ferritinophagy-protiens expressions, induce ferritinophagy to inhibit tumours finally. In vivo studies revealed the low toxicity of betulinic acid in mice, the dose of human was about 10 times that of mice, the using dose of human could also be achievable. These findings illustrate the potential of betulinic acid for treatment of cancer.